2013
DOI: 10.1017/s0950268813000319
|View full text |Cite
|
Sign up to set email alerts
|

Modifiable diarrhoea risk factors in Egyptian children aged <5 years

Abstract: By conducting a case-control study in two university hospitals, we explored the association between modifiable risk behaviours and diarrhoea. Children aged <5 years attending outpatient clinics for diarrhoea were matched by age and sex with controls. Data were collected on family demographics, socioeconomic indicators, and risk behaviour practices. Two rectal swabs and a stool specimen were collected from cases and controls. Samples were cultured for bacterial pathogens using standard techniques and tested by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 33 publications
1
12
1
Order By: Relevance
“…The first risk factor detected in this study is recurrent diarrhea, which is associated with malnutrition, failure to thrive, and adversely affects immunity so the child will be more susceptible to diarrhea ( p =0.001; OR=6.61; 95% CI: 3.41-12.90), which is similar to other studies. 13 - 17 The other risk factor is living in crowded houses, which increases susceptibility to diarrheal diseases (OR=0.02; 95% CI 1.03-4.01), which is similar to other studies. 6 , 8 , 11 , 14 Children who were incompletely vaccinated or not vaccinated at all were at risk for diarrheal diseases ( p =0.027; OR=2.02; CI: 1.08-3.80), again in agreement with other studies.…”
Section: Discussionsupporting
confidence: 87%
“…The first risk factor detected in this study is recurrent diarrhea, which is associated with malnutrition, failure to thrive, and adversely affects immunity so the child will be more susceptible to diarrhea ( p =0.001; OR=6.61; 95% CI: 3.41-12.90), which is similar to other studies. 13 - 17 The other risk factor is living in crowded houses, which increases susceptibility to diarrheal diseases (OR=0.02; 95% CI 1.03-4.01), which is similar to other studies. 6 , 8 , 11 , 14 Children who were incompletely vaccinated or not vaccinated at all were at risk for diarrheal diseases ( p =0.027; OR=2.02; CI: 1.08-3.80), again in agreement with other studies.…”
Section: Discussionsupporting
confidence: 87%
“…et al found that another member with diarrhea at home and no or faulty practices of hand washing also increases the diarrheal diseases. 29 In our study, instead of another diarrheal child in the same family, we had taken diarrheal child in the neighboring home.…”
Section: Discussionmentioning
confidence: 99%
“…In Egypt, intestinal parasitic infection in children is a common public health problem; in all governorates it was identified among infants, preschool and school children (Mansour et al, 2013). Though the reported prevalence rates in different parts of Egypt vary considerably from one study to another, however, nearly 27% of the children are suffering from intestinal parasites (Ibrahium, 2011).…”
mentioning
confidence: 99%